2020
DOI: 10.1016/j.metabol.2020.154222
|View full text |Cite
|
Sign up to set email alerts
|

DDB1 E3 ligase controls dietary fructose-induced ChREBPα stabilization and liver steatosis via CRY1

Abstract: Fructose over-consumption contributes to the development of liver steatosis in part by stimulating ChREBPα-driven de novo lipogenesis. However, the mechanisms by which fructose activates ChREBP pathway remain largely undefined. Here we performed affinity purification of ChREBPα followed by mass spectrometry and identified DDB1 as a novel interaction protein of ChREBPα in the presence of fructose. Depletion and overexpression of Ddb1 showed opposite effects on the ChREBPα stability in hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…( 41 ) We recently observed that fructose enhances ChREBP protein stability by inhibiting its proteolysis. ( 42 ) In contrast, very little is known about the effects of hepatocyte stress, such as APAP overdose, on the hepatic ChREBP pathway. APAP overdose causes cellular oxidative stress and mitochondrial impairment.…”
Section: Discussionmentioning
confidence: 99%
“…( 41 ) We recently observed that fructose enhances ChREBP protein stability by inhibiting its proteolysis. ( 42 ) In contrast, very little is known about the effects of hepatocyte stress, such as APAP overdose, on the hepatic ChREBP pathway. APAP overdose causes cellular oxidative stress and mitochondrial impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose transporter 5 is responsible for absorbing and metabolizing the majority (90%) of fructose into glucose and lactic acid in the small intestine, with only a small amount reaching the liver for further processing ( 54 ). Preclinical experiments showed that the expression and activity of ChREBP in the liver were improved in mice fed a high fructose diet ( 39 , 55 ). In the case of excessive fructose, the fructose absorbed by the intestine reaches saturation, and fructose turns into liver metabolism.…”
Section: The Disturbance Of Lipid Metabolism In Masldmentioning
confidence: 99%
“…In 2020, the epidemiological inquiry revealed that approximately 1.7 billion individuals worldwide have MASLD (3), and it is estimated that by 2030, approximately one third of the global population will be impacted by this disease (4). The prevalence of MASLD in the general population is around 6.3%-33% (5), 65% in obese people, 55.5% in people with diabetes, and as high as 72% in patients with dyslipidemia (4,6,7). Notably, the prevalence of MASLD tends to increase with advancing age, with less than 20% of cases observed in individuals below 20 years old and over 40% observed in those above 60 years old.…”
Section: Introductionmentioning
confidence: 99%
“…While allosteric activation of ChREBP might be required for its carbohydrate-sensing function, posttranslational modifications of ChREBP may alter protein stability, subcellular localization, protein-DNA or protein-protein interactions, all of which may alter the efficiency by which ChREBP transcribes its gene targets (32,33,35,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). For example, in the setting of hypoglycemia, ChREBP may be phosphorylated by cAMPdependent protein kinase and AMP kinases, which decrease the ability of ChREBP to enter the nucleus and bind DNA (39,40,43).…”
Section: Regulation Of Chrebp Activity By Carbohydrate Metabolitesmentioning
confidence: 99%